Translation and Validation of the Online Homework Distraction Scale for Peruvian University Students - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Sarria-Arenaza, Fiorella; Meza-Villafranca, Anahí; Paula Alfaro, Ana; Lingan, Susana K. (Frontiers in Education, 2022)
The objective of this study was to translate and validate the Online Homework Distraction Scale (OHDS) for Peruvian university students. Accordingly, an instrumental cross-sectional study was conducted with 811 university students, including students of both sexes aged between 16 and 39 (M = 20.96 years; SD = 4.42) residing in the city of Lima. The content-based validity evidence was analyzed using Aiken’s V coefficient based on the internal structure through a confirmatory factor analysis and considered in relation to other variables a through correlation analysis. The reliability was calculated using the Omega coefficient. Expert opinions were favorable for all items (V > 0.70). The one-dimensional structure of the scale was confirmed, and it presented acceptable reliability (α > 0.70). Thus, the OHDS for university students is a measure with a valid and reliable scale.